THE DEVELOPMENT OF SOCIAL BELONGING AND CHANGES IN LIFESTYLE FOR WOMEN IN FITNESS: CASE STUDY - Čuprika, Aleksandra; Fernāte, Andra; Čupriks, Leonīds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Fitness as a healthy lifestyle implementation helps to improve the social, mental and physical well-being components. Several scientists have indicated that there is a connection between social belonging and physical activity (PA) as the structural component of a healthy lifestyle (Walseth, 2006; Walseth & Fasting, 2004; Antonsich, 2010; Yuval-Davis, 2006; Anthias, 2006; Pinquart & Sorensen, 2001; Everard et. al., 2000). That is why the goal of the research is to develop and apply a social belonging promotion programme for women in fitness programme and to determine the changes in the lifestyle structural component health promoting PA. 10 women involved in fitness classes in small groups (2-4 people) participated in the case study, where in addition to PA social belonging promotion events were organized for all women together. In order to evaluate the structural components of social belonging and PA level and type, questionnaires adapted in Latvia and a semi-structured interview was used. Applying the social belonging promotion programme for women in fitness creates statistically significant changes in such structural components as sense of commitment (p<0.01), perception of interpersonal relations (p<0.01). By additionally promoting social belonging in fitness, women perceive the group better, are willing to spend more time with it; that, in turn, positively affects the willingness to be physically and socially active on a daily basis.